PENGEMBANGAN TES PILIHAN GANDA MENGGUNAKAN MODEL RASCH MATERI GERAK LURUS KELAS X PONTIANAK - Muhammad Ramadhan Ridho Novinda; Haratua Tiur Maria Silitonga; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract This study aimed to create multiple choice objective test on linear motion to measure the learning outcomes of X grade high school students in Pontianak City. The method used was Research and Development (R & D) with the Four-D models. Development tests using Mardapi steps which has 9 steps. Consisting 40 item of tests. Trial questions involved 33 students in small-scale trials, and 204 students in large-scale trials. Item characteristics were analyzed using the Winstep program with the Rasch Model. Based on the analysis of the data, it can be concluded that the test developed worthy of use to measure student learning outcomes are: 1) items made with simple language with a readability level of 6.60, 2) a high level of content validity which is equal to 0.75, 3) all items spread evenly on person-item maps, 4) there are 28 items which are included in the easy to hard category, 5) the value of unidimensionality which includes enough categories is 31%, 6) the value of items reliability that belong to the special category is equal to 0,98. Based on the result of the analysis, there are 26 items that are worthy of use. Keywords: Linear Motion, Rasch Model, Test Development.